EVALUATION PROGRAM OF DEVELOPMENT AND TRAINING CENTER SPORTS STUDENTS (PPLP) in YOGYAKARTA - Asmawi, Moch.; Surono, S (Program Pascasarjana Universitas Negeri Jakarta, 2016)
The purpose of this study is to evaluate the Program Development and Training Center Sports Student (PPLP) in Yogyakarta.The research method was used research evaluation. This program evaluation is using CIPP (Context, Input, Process, and Product) model of Stufflabeam. The data in this study were collected through interviews, questionnaires and document study. Respondents were used to obtain data through interviews related to the implementation of the Program Development and Training Center Sports Student (PPLP) Yogyakarta is athletes, coaches, of BPO DIY. Interview data collected, and then reduced to obtain conclusions. The results based on components of CIPP through questionnaire distributed to 30 respondents. 30 responses were 6.67% of the respondents stated very well, 83.33% said good and 10% said enough.